An Economic Analysis of Green Environment and Sustainable Development in India - Rathna Y.D. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The economic analysis of the green environment and sustainable development in India explores the balance between economic growth and ecological preservation. India’s approach to sustainable development involves integrating environmental policies with economic planning to ensure long-term prosperity without resource depletion. Rapid GDP growth, while uplifting millions from poverty, has intensified environmental pressures—manifested in pollution, deforestation, and high carbon emissions. Reports by the World Bank and The Energy and Resources Institute highlight that green growth models can lessen these challenges through efficient resource use, renewable energy adoption, and ecosystem service valuation. India’s transition toward a green economy is driven by commitments to the Paris Agreement and national programs such as renewable energy expansion, waste management, and carbon intensity reduction. Estimates suggest that by implementing green strategies, India can sustain its growth at a marginal economic cost of just 0.02–0.04% of annual GDP while achieving significant environmental and social benefits. However, fiscal constraints, technological adaptation, and inequality remain major policy hurdles. An integrated green economy framework—using tools like computable general equilibrium models—demonstrates that green investments can improve employment, health, and productivity while safeguarding natural capital. Consequently, the pursuit of sustainable development in India signifies not a trade-off but an opportunity to modernize its economic structure and align growth with environmental equity, securing intergenerational welfare and resilience to climate risks.